STUDY OF BLENDING OF COAL COMBUSTION PRODUCT FROM COAL FIRED POWER PLANT WITH POTENTIALLY ACID FORMING MATERIAL TO PREVENT ACID MINE DRAINAGE. - Firman
Acid Mine Drainage (AMD) is one of environmental concerns of mining activities and need to be prevented. One of AMD prevention method is passive method by blending PAF Material with Non-Acid Forming Material. One of constraint often faced by mining companies is the limitation of NAF material. Other Non-Acid Forming Material that is available and abundant near mine site is Coal Combustion Product (CCP) from Mine-Mouth Coal-Fired Power Plant. The Study of usage of CCP as a blending material with PAF material in order to prevent AMD is deemed necessary. This study consist of several methods: grain-size analysis and distribution, XRD test, ICP-MS test, Static Test, Kinetic Test and Water Quality Test. The static test is done to characterize the potency of material to produce acid mine drainage. Kinetic test is done using Free Draining Column Leach Test (FDCLT) method. Different blending simulations of varying PAF material size (fine and coarse), varying CCP-PAF Material ratio (2:1; 1:1; and 0,5:1 by weight) and varying CCP material (FA BJS, BA BB and BA BB) are made and leachate water from kinetic test is physically and chemically tested. Analysis of reaction using abovementioned data is made by using software PHREEQC to calculate acid-base equibrium, dissolution rate of alkalinity-producing mineral and oxidizing rate of pyrite of blending material. The rates are governed by decaying equation (1storder differential equation) This study result shows that variation in OB-Claystone grain size is not influencing the acidity of leachate water. Blending FA-BJS with OB-CS with minimum ratio of 1,12:1 (by weight) is effective to prevent AMD generation. In other hand, blending of OB-CS with BA BB and BA BJS with minimum ratio of 5,7:1 and 6,9:1 respectively is effective to prevent AMD generation. Acid-base equibrium is met when ratio of mole-transfer between neutralizing mineral (peliclase, aragonite) to acid-generating mineral (pyrite) is 1:1 (by weight). The higher ratio of FA/BA in blending, the lower oxidation and alkalinity-production rate. Rate of oxidation of pyrite and alkalinity-production rate is the same at OBCS and FA-BJS blending ratio of 1:1,62 (by weight)